Judging Foreign States - Zachary D. Clopton (Washington University Law Review, 2016)
Famed foreign relations law principles, including the act of state doctrine, the public law taboo, and Zschernig’s foreign affairs preemption, rely on the notion that U.S. courts should not sit in judgment on foreign states. Judges in these cases, as well as scholars writing in the area, frequently suggest that U.S. courts should sit out of important disputes due to considerations of sovereign equality and international comity. Yet, in less attention-grabbing cases, U.S. courts routinely sit in judgment on foreign judgments, laws, legal systems, and interests, sometimes concluding that they do meet U.S. standards. The first goal of this project, therefore, is to identify and catalog those circumstances in which U.S. courts sit in judgment on foreign states. This extensive catalog should cast doubt on unsystematic objections to sitting in judgment: Were we to accept that sitting in judgment was per se impermissible, all sorts of current doctrines would need to be revisited. Such a categorical rule is not only radical, but also unjustified. The doctrines in which courts sit in judgment are routine and unremarkable; they protect important institutional and individual concerns; and they have not sparked international incident. Nor is there a coherent distinction between the doctrines that call for courts to sit in judgment and those that do not. Identifying these issues does not determine a better approach, and recent scholarship on these and related cases have proposed changes to U.S. law that turn on external considerations such as foreign interests or international comity. But this literature, in my view, risks focusing too much on the transnational aspects of these cases to the exclusion of domestic institutional concerns. As a potential corrective, this Article imagines sitting-in-judgment doctrine that is responsive to those structural factors that govern institutional arrangements within the U.S. system. Applying the tools of comparative institutional analysis, cases could be divided into those bilateral, legal, and constrained adjudications for which the common-law courts were designed, versus those polycentric, systemic, political inquiries best left to the political branches. Federalism, with implications for both authority and capacity, would suggest further division of responsibilities among relevant institutions. And individual-rights considerations would offer guidance to courts about how to sit in judgment when called upon to do so. This analysis demonstrates not only that there is no per se reason that U.S. institutions should avoid sitting in judgment on foreign state acts, but also that current law may not be allocating responsibility for sitting in judgment consistent with domestic institutional considerations
Keywords: foreign relations; international law; US constitution; judgments; foreign legal systems